A Texonomy on Web Page Categorization - Bhavana; Raheja, Neeraj (International Journal of Computer Sciences and Engineering, 2019)
Web Page Categorization becomes essential due to the increase in the information on the Internet. As pages on the web are growing regularly and can cover almost all types of information. However finding accurate and useful information from these large amounts of web pages for a user is difficult, so efficient and accurate methods for categorizing this large of information is very necessary. Web page categorization is to categorized web pages into specified categories. It improves the efficiency of search on the web. This paper discusses various methods, approaches & uses of web page categorization.